Answer:
Step 1: Distribute 1.2 to 6.3 and –7x
Step 2: Combine 3.5 and 7.56
Step 3: Subtract 11.06 from both sides
Explanation:
Given the expression 3.5 + 1.2(6.3 – 7x) = 9.38, we are to write the possible steps involved in solving the equation
3.5 + 1.2(6.3 – 7x)
Step 1: Distribute 1.2 to 6.3 and –7x
3.5 + 1.2(6.3 – 7x) = 9.38
3.5 + 1.2(6.3) + 1.2(-7x) = 9.38
3.5 + 7.56 - 8.4x = 9.38
Step 2: Combine 3.5 and 7.56
11.06 - 8.4x = 9.38
Step 3: Subtract 11.06 from both sides
11.06 - 8.4x - 11.06 = 9.38 - 11.06
-8.4x = -1.68
Step 3=4: Divide both sides by -8.4
-8.4x/-8.4 = -1.68/-8.4
x = 0.2
Hence the three steps are
Step 1: Distribute 1.2 to 6.3 and –7x
Step 2: Combine 3.5 and 7.56
Step 3: Subtract 11.06 from both sides